Congenital Cyst of the Pancreas: A Case Report and Review of Literature. (3rd July 2016) - Warnock, William T.; Khoshnam, Nasim; Bird, Kristin M.; Schaffer, Lauren R.; Lou, L. H.; Hawkins, C. Matthew; Santore, Matthew T.; Hill, Sarah; Gill, Anne E.; Hoseinzadeh, Pooya; Shehata, Bahig M.
ABSTRACT: This is a case of a newborn female with congenital pancreatic cysts discovered incidentally. The 5-week-old infant had multiple abdominal cysts originating from the pancreas. When the radiologist catheter placement failed to alleviate the symptoms, the infant underwent laparoscopic excision. The lesion, however, recurred 11 months after the first excision, leading to a second surgical procedure including excision and marsupialization. A review of the literature revealed that this is a rare condition. Herein, we discuss the characteristics of the case, including medical imaging, drainage catheter placement, surgical treatment, pathological findings, and follow-up. Differential diagnoses, clinical presentations, treatment options, and patient outcomes are also discussed. Although rare, congenital pancreatic cyst should be considered in the differential diagnosis of an infant with cystic lesion of the pancreas.